1979
DOI: 10.1128/jb.137.1.692-693.1979
|View full text |Cite
|
Sign up to set email alerts
|

Simple method for identification of plasmid-coded proteins

Abstract: Proteins encoded by plasmid DNA are specifically labeled in UV-irradiated cells of Escherichia coli carrying recA and uvrA mutations because extensive degradation of the chromosome DNA occurs concurrently with amplification of plasmid DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
247
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,040 publications
(254 citation statements)
references
References 10 publications
6
247
1
Order By: Relevance
“…Analysis of the polypeptides encoded by the plasmid pTK806-1 and its deletion derivatives was by the maxicell technique (C). E.coli XL1 cells harboring the respective plasmids were converted to maxicells according to Sancar et al (1979). After labelling with L-[35S]methionine the polypeptides were characterized by 0.1 % SDS-12% PAGE (Laemmli, 1970), and the labelled proteins were visualized by fluorography of the stained and dried gel.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the polypeptides encoded by the plasmid pTK806-1 and its deletion derivatives was by the maxicell technique (C). E.coli XL1 cells harboring the respective plasmids were converted to maxicells according to Sancar et al (1979). After labelling with L-[35S]methionine the polypeptides were characterized by 0.1 % SDS-12% PAGE (Laemmli, 1970), and the labelled proteins were visualized by fluorography of the stained and dried gel.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the permease is making use of the existing proton gradient in accordance with the chemiosmotic theory of Mitchell (1970). In Escherichia coli, it was found that the uracil permease gene of similar plasmids is transcribed into RNA, but no translation product was detected in the maxicell system described by Sancar et al (1979). Therefore, we could not test the functioning of the eucaryotic permease in a procaryotic membrane.…”
Section: Discussionmentioning
confidence: 94%
“…In ASA-dehydrogenase, Cys135 might play a similar role, even though the amino-acid sequences around the reactive cysteine residue in GPDH and ASA-dehydrogenase show no homology. Expression of the asd gene is very efficient in the cell: the protein can already be detected in crude extracts after electrophoresis in polyacrylamide gels (using a deletion strain as a control; data not shown); using the maxicell technique with strain CSR603 (Sancar et al, 1979) harboring pAD20, the band corresponding to ASA-dehydrogenase is even more intense that the one due to ,3-lactamase (data not shown). This high level of expression can be accounted for by the following observations obtained from the sequence data: (1) a preferential use of the frequent codons as discussed above; (ii) a convenient sequence of ribosome binding, AGGA, though somewhat distant (11 bp) from the initiation ATG; (iii) the existence, at positon 168, of a sequence TATGGTG very similar to the consensus Pribnow box, preceded by a TTG region, in good agreement with the canonical -35 sequence (Rosenberg and Court, 1980).…”
Section: Discussionmentioning
confidence: 99%